Evaluation of a polymorphism in MYBPC3 in patients with anthracycline induced cardiotoxicity - M. Thirumalai Vinodhini; S. Sneha; R.P. Nagare; S. Bindhya; V. Shetty; D. Manikandan; P. Ganesan; T.G. Sagar; T.S. Ganesan (Indian Heart Journal, 2018)
Cardiotoxicity is the most serious side effect of anthracyclines (doxorubicin, daunorubicin or epirubicin). The incidence of anthracycline induced late cardiac toxicity (AIC) that is overt clinically is 3–5% in the Indian population. Polymorphism in intron 32 (deletion of 25 bp) of MYBPC3 has been shown to be present exclusively in Asians and more so in South India (3–8%). The frequency of the polymorphism is significantly higher (13%) in patients with cardiomyopathy in India. Fifteen patients were identified to have cardiac dysfunction following treatment for malignant lymphoma with doxorubicin containing regimens. Peripheral blood DNA from control, amplified by polymerase chain reaction yielded a 467 bp fragment while in the presence of the 25 bp deletion only a 442 bp fragment was detected. To confirm the presence or absence of the polymorphism, amplified DNA was restricted using Bgl1 in all samples. Bgl1 restricted amplified DNA only if the 25 bp deletion was absent. A 467 base pair band was observed in all the 15 samples, which suggested the absence of polymorphism in MYBPC3. In a sample of DNA from a patient with a deletion in exon 33 (confirmed by sequencing) a 442 bp fragment was detected. Amplified DNA from this patient was not restricted with Bgl1. Wild type MYBPC3 when amplified gave a distinct restriction banding pattern consisting of two bands of 401 bp and 66 bp. Amplified DNA from all peripheral blood samples restricted with Bgl1 suggesting the absence of the polymorphism. In this preliminary report, MYBPC3 does not seem to play a role in anthracycline induced cardiotoxicity. Keywords: MYBPC3, Polymorphism, Anthracycline, Cardiotoxcity